Impact of drug interactions, dosage, and duration of therapy on the risk of hip fracture associated with benzodiazepine use in older adults - Zint, Kristina; Haefeli, Walter E.; Glynn, Robert J; Mogun, Helen; Avorn, Jerry; Stürmer, Til (Pharmacoepidemiology and drug safety, 2010)
To determine how concomitant use of potentially interacting drugs, drug dosage, and duration of therapy modify the risk of hip fracture associated with use of benzodiazepines and benzodiazepine-related drugs (BDZ) in older adults.